The role of microRNA in metastatic processes of non-small cell lung carcinoma - Pastorkova, Zuzana; Skarda, Jozef; Andel, Jozef (Biomedical papers, 2016)
Background: MicroRNAs are small non-coding one-stranded RNA molecules that play an important role in the post-transcriptional regulation of genes. Bioinformatic predictions indicate that each miRNA can regulate hundreds of target genes. MicroRNA expression can be associated with various cellular processes leading to the metastasis of malignant tumours including non-small cell lung carcinoma. This review summarizes current knowledge on the role of microRNAs in NSCLC metastasis to the brain and lymph nodes.Methods. A search of the NCBI/PubMed database for publications on expression levels and the mechanisms of microRNA action in NSCLC metastasis.Results and Conclusion: Dysregulation of microRNAs in NSCLC can be associated with brain and lymph node metastasis. There are differences in microRNA expression profiling between NSCLC with and without metastases but it is currently not possible to reliably predict the site of metastasis in NSCLC. Based on data from RNAmicroarrays, bioinformatics analysis is able to predict the target genes of highlighted microRNAs, providing us with complex information about cancer cell features such as enhanced proliferation, migration and invasion. Such microRNAs may then be knocked-down using siRNAs or substituted with miRNA mimics. RNA microarray profiling may thus be a useful tool to select up- or down-regulated microRNAs. A number of authors suggest that microRNAs could serve as biomarkers and therapeutic targets in the treatment of NSCLC metastasis.
Keywords: microRNA; non-small cell lung carcinoma; brain metastasis; lymph node metastasis